Keterampilan Productive Pedagogies Calon Guru Biologi Pada Pelaksanaan Pembelajaran di Era Pandemi - Iffa Ichwani Putri; Nurul Fauziah (Pedagogi Hayati, 2021)
This study aims to determine the productive pedagogies skills of prospective teachers in implementing learning in the pandemic era. These skills indicate the professional level of a teacher in carrying out their duties. Ideally the teacher should be able to show every dimension of productive pedagogies during the learning process. Productive pedagogies of a teacher can be seen from three dimensions, namely intellectual quality, relevance, and mastery of the classroom environment. The implementation of this descriptive research is carried out in the implementation of teaching by biology education teacher candidate students who do Field Experience Practices. Productive pedagogies are measured using a Likert scale questionnaire and observation sheets on the implementation of learning. The data obtained were analyzed on the conversion of values ​​with the low to high category, and then the comparison was carried out using the scheme to provide a description of the productive pedagogies' domination. The research findings show that the productive pedagogies of biology teacher candidates based on a questionnaire (85.75) and the implementation of learning (93.00) are in the very good category. The rating of each dimension of productive pedagogies is in the very good category. It can be concluded that prospective biology teachers are considered ready to face learning situations both offline and online with good learning strategies.